PROBLEMS OF ETHNOCULTURAL SPACE OF THE AR OF CRIMEA IN THE CONTEXT OF THE ANNEXATION OF THE PENINSULA - Hazizova, Olena (Київський національний університет імені Тараса Шевченка, 2018)
The Crimean Tatar problem holds a leading position in the system of ethnocultural relations with the AR of Crimea. It is caused by a number of factors inherited from the past, as well as by the imperfection of the legislative basis of Ukraine, its ethnonational policy. Political and legal foundation, built during the years of independence, made it possible to combine the interests of all components of the Ukrainian political nation; however, it didn’t provide equal conditions for the ethnonational development and active participation in state-building processes of Crimean Tatars and national minorities. According to the All-Ukrainian Population Census of 2001, the ethnic composition of the Autonomous Republic of Crimea is as follows: Ukrainians constitute 24.3%, Russians – 58.3%, Crimean Tatars – 12.0%, other nationalities – 5.4% (Belarusians – 1.4%, Tatars – 0,5%, etc.). Separate statistics regarding the city of Sevastopol indicated the prevalence of Russians (71.6%); almost the statistically average percentage of Ukrainians in Crimea (22.4%); and a small Crimean Tatar community (0.5%). During the years of independence, the national and cultural need of Ukrainians and Crimean Tatars to study in their mother tongues was extremely poor. So, out of 583 schools that functioned in Crimea in 2014, only 7 were Ukrainian, and from 23.4% of ethnically Ukrainian schoolchildren only 0.7% were taught in the state language. In the 2013–14 academic year, 5551 Crimean Tatar children were educated in their native language; the national-cultural needs of the Crimean Tatars were not completelythis situation was the lack of qualified pedagogical staff, lack of textbooks, etc. After the annexation of Crimea, the Ukrainian language, which the occupation government had recognized as one of the state languages, almost completely disappeared from the educational space of Crimea, with only 1 of 7 schools retaining Ukrainian-language instruction. Today, 15 general education establishments of the Republic of Crimea continue to provide their instruction in the Crimean Tatar language (201 classes, 3651 students). Long before the onset of the armed conflict in eastern Ukraine and the annexation of Crimea, challenges in the humanitarian field, in particular the tragedy of the Ukrainian language in the cultural and educational continuum of the peninsula, were in the sight of the Ukrainian humanities: lead scientists observed negative ethnocultural tendencies caused by the inaction of state authorities that reinforced the threat of disintegration and loss of state sovereignty. During the years of Ukrainian independence, Crimea hasn’t formed strong pro-Ukrainian electorate capable of defending state sovereignty. Taking into account the constant support of Russia by the Russian community of the peninsula, lobbying for the idea of the “Russian World” and “the originally Russian Crimea”, as well as the lame state support of Ukrainian and Crimean Tatar communities, which would be able to withstand the separatist threats, the ideological war in Crimea had been lost even before 2014, which became one of the reasons for the annexation of the peninsula. Key words: national culture, AR of Crimea, annexation, Ukrainians, Crimean Tatars, Russians, humanitarian challenges.

В системі етнокультурних взаємин в АР Крим ключове місце посідає кримськотатарська проблема, зумовлена як низкою успадкованих від минулого факторів, так і недосконалістю законодавчої бази України, її етнонаціональної політики. Сформована за роки незалежності політико-правова база створила підґрунтя для гармонійного поєднання інтересів усіх складових української політичної нації, однак вона недостатньо забезпечила рівні умови для етнонаціонального розвитку й активної участі у державотворчих процесах кримськотатарського народу та національних меншин. За даними Всеукраїнського перепису населення України 2001 р., в Автономній Республіці Крим проживало 24,3 % українців, 58,3% – росіян, 12,0% – кримських татар, 5,4 % – інших національностей, зокрема, білорусів – 1,4 %, татар – 0,5 % та ін. Окрема статистика по місту Севастополю свідчить про переважання російського населення (71,6 %), майже середньостатистичний по Криму відсоток українців (22,4 %) та про нечисельну кримськотатарську громаду (0,5 %). За роки незалежності національно-культурні потреба українців і кримських татар задовольнялися вкрай погано. Так, з 583 шкіл, що функціонували у Криму в 2014 р., лише 7 були україномовними, а з 23,4% школярів – етнічних українців – державною мовою навчалися лише 0,7 %. У 2013/14 навчальному році рідною мовою здобували освіту 5551 кримськотатарська дитина, національно-культурні потреби кримських татар не задовольнялися повністю, кількість навчальних місць в кримськотатарських класах не відповідала реальним потребам. Однією з причин такої ситуації була відсутність кваліфікованих педагогічних кадрів, недостатнє забезпечення навчальною літературою тощо. Після анексії Криму українська мова, яку окупаційна влада визнала однією із державних, майже повністю зникла з освітнього простору Криму, із 7 шкіл з українською мовою навчання залишилась тільки 1. У Республіці Крим продовжує функціонувати 15 загальноосвітніх закладів з кримськотатарською мовою навчання (201 клас, 3651 учень). Виклики в гуманітарній сфері, зокрема упосліджене становище української мови в культурно-освітньому континуумі Криму, задовго до початку збройного конфлікту на сході України та анексії АР Крим знаходилися у полі зору української гуманітаристики, провідні науковці вказували на негативні етнокультурні тенденції, викликані бездіяльністю органів державної влади, що підсилювали загрози дезінтеграції та втрати державного суверенітету. За роки незалежності України в Криму не було сформовано сильного проукраїнського електорату, здатного до відстоювання державного суверенітету. Враховуючи постійну підтримку Росією російської громади півострова, лобіювання ідеї «руського мира» та «исконно русcкого Крыма» і недостатню підтримку Україною української та кримськотатарської громад, які здатні були б протистояти сепаратистським загрозам, ідеологічна війна на теренах Криму була програна ще до 2014 р., що стало однією з причин анексії півострова. Ключові слова: національна культура, АР Крим, анексія, українці, кримські татари, росіяни, гуманітарні виклики.
ПРОБЛЕМИ ЕТНОКУЛЬТУРНОГО ПРОСТОРУ АР КРИМ В КОНТЕКСТІ АНЕКСІЇ ПІВОСТРОВА